Peroxisome proliferator-activated receptor-γ (PPARγ) agonist is neuroprotective and stimulates PGC-1α expression and CREB phosphorylation in human dopaminergic neurons. (March 2016) - Mäkelä, Johanna; Tselykh, Timofey V.; Kukkonen, Jyrki P.; Eriksson, Ove; Korhonen, Laura T.; Lindholm, Dan
Abstract: Mitochondrial dysfunction has been linked to several neurodegenerative diseases such as Parkinson's disease (PD). Peroxisome proliferator-activated receptor-γ coactivator-1α (PGC-1α) is a master gene for mitochondrial biogenesis and has been shown to be neuroprotective in models of PD. In this work we have studied the mechanisms by which peroxisome proliferator-activated receptor-γ (PPARγ) selective agonist N -(2-benzoylphenyl)- O -[2-(methyl-2-pyridinylamino)ethyl]-l -tyrosine hydrate (GW1929) acts on human dopaminergic neurons in culture. Data showed that GW1929 increased the viability of human dopaminergic neurons and protected them against oxidative stress induced by H2 O2 and the mitochondrial toxin Rotenone. The enhanced resilience of the neurons was attributed to increased levels of mitochondrial antioxidants and of PGC-1α. GW1929 treatment further increased cell respiration, mitochondrial biogenesis and sirtuin-1 (SIRT1) expression in the human dopaminergic neurons. Phosphorylation of cAMP responsive element-binding protein (CREB) was also robustly increased in GW1929-treated cells. Together these results show that the PPARγ agonist GW1929 influences CREB signaling and PGC-1α activities in the human dopaminergic neurons contributing to an increased cell viability. This supports the view that drugs acting on the PPARγ-PGC-1α signaling in neurons may have beneficial effects in PD and possible also in other brain disorders. Graphical abstract: Highlights: Mitochondrial dysfunctions contribute to the pathogenesis of Parkinson's disease (PD). PPARγ is a transcription factor with metabolic functions in the body. PGC-1α is a master regulator of mitochondrial biogenesis and cell viability. PPARγ agonist increased PGC-1α and cell respiration in human dopaminergic neurons. PPARγ agonist increased the phosphorylation of CREB and AC6 levels in the neurons.